Spirit of Place Analysis of Bandar Lampung Teluk Market as The Act of Heritage Conservation - S I, Ishar; I, Sadad (International Conference on Engineering and Technology Development (ICETD), 2017)
Bandar Lampung Teluk Market Area is an important areaforming Bandar Lampung city in the past. This area is an economic milestone in the city and is known as a strategic trading area since 1839. Its position which directly tangent to the coastal areasinvites migrants from all over the country to trade. Starting from the superior potential of seafood, Teluk Marketoffers an increasingly diverse variety of commodities. Starting from the needs of food, clothing to the entertainment. Cultural diversity of people around the Teluk Market coming from all over the country offers a multi-ethnic nuance and creates variety of unique food whichfinally became the famous culinary in the city until now. Not only known as a trading center, Teluk Market is also known as the lifestyle center in its heyday. These potentials leave a nostalgic atmosphere to the area. The area is surrounded by the architecture of Dutch heritage buildings, old pagoda, and old shops that aged over 60 years. But as the era progressed, precisely since 1984 where Tanjung Karang and Teluk Betung merged into a single city (known as Bandar Lampung), this area is getting less interested by the visitors. Teluk Market is seen as an untapped old trading area. The development and construction of Bandar Lampung City concentrates more on Tanjung Karang which is now increasingly filled with modern shopping centers. Teluk Market continued to fade in popularity compared to modern mall markets.Therefore, this study aims to rediscover the spirit of place in the Teluk Market area and then introduce it back to the community as one of the identity of Bandar Lampung City. This research will analyze the spirit of place of this region by way of; 1) analyzing the spirit of place in terms of the architecture of the old buildings by identifying the style and age of the buildings; 2) analyzing the perceptions of surrounding communities. This research will result building typology and community perception of Teluk Market which can be used as a foundation in conserving and developing Teluk Market area as a heritage area